Co-exposure to lead, mercury, and cadmium induces neurobehavioral impairments in mice by interfering with dopaminergic and serotonergic neurotransmission in the striatum - Pyatha, Sarita; Kim, Haesoo; Lee, Daeun; Kim, Kisok (Frontiers in Public Health, 2023)
Humans are exposed to lead (Pb), mercury (Hg), and cadmium (Cd) through various routes, including drinking water, and such exposure can lead to a range of toxicological effects. However, few studies have investigated the toxic effects of exposure to mixtures of metals, particularly in relation to neurotoxicity. In this study, 7-week-old male mice were exposed to Pb, Hg, and Cd individually or in combination through their drinking water for 28 days. The mice exposed to the metal mixture exhibited significantly reduced motor coordination and impaired learning and memory abilities compared to the control group and each of the single metal exposure groups, indicating a higher level of neurotoxicity of the metal mixture. The dopamine content in the striatum was significantly lower in the metal mixture exposure group than in the single metal exposure groups and the control group. Furthermore, compared to the control group, the metal mixture exposure group showed a significantly lower expression level of tyrosine hydroxylase (TH) and significantly higher expression levels of dopamine transporter (DAT), tryptophan hydroxylase 1 (TPH1), and serotonin reuptake transporter (SERT). Notably, there were no significant differences in SERT expression between the single metal exposure groups and the control group, but SERT expression was significantly higher in the metal mixture exposure group than in the single metal and control groups. These findings suggest that the key proteins involved in the synthesis and reuptake of dopamine (TH and DAT, respectively), as well as in the synthesis and reuptake of serotonin (TPH1 and SERT, respectively), play crucial roles in the neurotoxic effects associated with exposure to metal mixtures. In conclusion, this study demonstrates that simultaneous exposure to different metals can impact key enzymes involved in dopaminergic and serotonergic neurotransmission processes, leading to disruptions in dopamine and serotonin homeostasis and consequently a range of detrimental neurobehavioral effects.